1997
DOI: 10.1007/bf02070706
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate analysis of the prognostic factors of patients with unresectable synchronous liver metastases from colorectal cancer

Abstract: Longevity of patients with unresectable synchronous liver metastases from colorectal cancer is affected adversely by the presence of nodal metastases and extent of liver metastases. This should be considered in the planning treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 8 publications
1
19
0
Order By: Relevance
“…Yamamura et al. [44] reviewed 73 cases with unresectable synchronous liver metastasis. They were divided into H1 (unilobar), H2 (< 4 bilobar) and H3 (> 5 bilobar).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Yamamura et al. [44] reviewed 73 cases with unresectable synchronous liver metastasis. They were divided into H1 (unilobar), H2 (< 4 bilobar) and H3 (> 5 bilobar).…”
Section: Resultsmentioning
confidence: 99%
“…Survival in the resected group might also improve because these patients are less likely to develop obstruction and perforation. Irinotecan and oxaliplatin Raised liver enzymes, age > 75 ***** Yun et al 43 Liver, peritoneum, lung 503 CEA, differentiation, resection, chemotherapy ******* Rosen et al 16 Liver, peritoneum 125 Age > 65, extensive liver involvement, carcinomatosis ******* Yamamura et al 44 Liver, peritoneum 73 Extent of liver metastases, number of nodes involved ****** Stelzner et al 45 Mainly liver 186 Performance status, CEA, metastatic load, chemotherapy ****** Goslin et al 46 Mainly liver 125 Metastatic load, degree of tumour differentiation ****** have been shown to result in significantly prolonged survival [51]. In the present review, four studies [28,[31][32][33] reported curative procedures in patients only with liver metastasis, after chemotherapy had shrunk the metastatic deposits.…”
Section: Discussionmentioning
confidence: 99%
“…Steele and Ravikumar 15 reported a median survival of 24 months in asymptomatic patients with three or fewer unresected metastases and 10 months for those with four or more. Scheele et al 16 reported a median survival of 14 months for patients with one to three unresected liver metastases, and Yamamura et al 17 reported a median survival of 13 and 12 months for patients with unresected metastases in one lobe and fewer than four metastases in both lobes, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Of twenty-three full-text articles that were excluded, twelve had no comparator nonsurgical group [27][28][29][30][31][32][33][34][35][36][37][38] ; four used a non-resection group (that is, ostomy procedures) as comparators [39][40][41][42] ; and another four used patients who underwent curative surgery as the comparator group [43][44][45][46] . Two studies, each with four comparator groups, provided minimal information about those groups, and one had a patient population that overlapped with the population of another study included in the present review 14,47 .…”
Section: Study Selectionmentioning
confidence: 99%